Balancing Value with Affordability: Cell Immunotherapy for Cancer Treatment in the U.S. (11th May 2020) - Leech, Ashley A.; Neumann, Peter J.; Cohen, Joshua T.; Jagasia, Madan; Dusetzina, Stacie B.
Abstract: Despite the Centers for Medicare and Medicaid Services' recent approval to increase payments for inpatient‐delivered chimeric antigen receptor T‐cell therapy (CAR‐T) for adult lymphoma, reimbursement remains far below the costs of the product and overall treatment of the therapy. We surveyed 92 CAR‐T‐certified centers in the U.S. to assess the perceived financial viability and related challenges for treating adult patients with lymphoma. Of 92 certified CAR‐T centers in the U.S., 20 (22%) directors or chief medical officers responded. More than three quarters of facilities reported treating patients in an inpatient setting, and 60% reported that the majority of their patients were covered under commercial/private insurance. The financial viability rating across centers (median: 62; interquartile range: 48–69; scale 1–100) signals that economic sustainability of institutional programs for adult lymphoma is a concern. These dynamics may limit access to CAR‐T for Medicare beneficiaries and lead to greater outpatient use of the therapy, which may limit access for medically complex patients. Abstract : CAR‐T represents one of the first of many anticipated ultra‐high‐priced treatments for rare or previously incurable conditions, making its successful integration into clinical practice and reimbursement models a useful example for gene and cell therapy adoption. This article focuses on the perceived financial viability and related challenges for CAR‐T among officials at CAR‐T certified centers across the U.S. for adult patients with lymphoma.